2015
DOI: 10.1016/j.acmx.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Apnea obstructiva del sueño y cardiopatía isquémica. Las evidencias de su relación

Abstract: The purpose of this review is to analyse the relation between obstructive sleep apnea and coronary disease. We present epidemiological data on the respiratory disorder and its association with ischemic cardiopathy, as well as common cardiovascular risk factors, physiopathological interactions between both conditions, clinical evolution and impact of treatment on prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(58 reference statements)
1
0
0
Order By: Relevance
“…Likewise, it was evident that in the group of patients with severe OSA, there were a greater number of patients with AHT. The relationship between OSA and AHT has been reported previously, and in accordance with the results, González-Pliego et al [ 36 ] reported the coexistence between OSA and AHT, relating OSA as one of the most common causes of secondary AHT. Likewise, Latorre et al [ 23 ] and Rimoldi et al [ 37 ] reported an association between AHT and OSA.…”
Section: Discussionsupporting
confidence: 86%
“…Likewise, it was evident that in the group of patients with severe OSA, there were a greater number of patients with AHT. The relationship between OSA and AHT has been reported previously, and in accordance with the results, González-Pliego et al [ 36 ] reported the coexistence between OSA and AHT, relating OSA as one of the most common causes of secondary AHT. Likewise, Latorre et al [ 23 ] and Rimoldi et al [ 37 ] reported an association between AHT and OSA.…”
Section: Discussionsupporting
confidence: 86%